Media components exploitation using Plackett-Burman design for citric acid production from paddy straw - Hayder Kh., Q. Ali; Mohamed Zulkali, Mohamed Daud (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Kampus Pauh Putra, Arau, Perlis, Malaysia.